Evaluating the Effectiveness of Phase-Change Material (PCM) Integrated Facades in Enhancing Thermal Comfort through Occupant Perception - Ma'in F. Abu-Shaikha; Mutasem A. Al-Karablieh; Odai S. Alabadleh; Razan Y. Al-Abed (International Journal of Computational and Experimental Science and Engineering, 2025)
This study investigates the impact of phase change material (PCM) integrated facades on indoor thermal comfort and occupant perception using a quantitative approach. A structured questionnaire was employed to assess thermal responses across different age groups. Results indicate that PCM facades significantly reduce indoor temperature fluctuations and improve thermal stability, with paraffin-based PCMs demonstrating superior heat absorption and release capabilities. However, occupant perception of comfort exhibited variability, suggesting additional influencing factors such as ventilation and metabolic differences. The study highlights the need for climate-specific PCM applications and improved material integration strategies. Future research should explore long-term PCM performance across diverse climates to optimize sustainable building design and enhance occupant thermal satisfaction.